Persepsi Perawat Tentang Spiritual Care di Ruang Intensive Care Unit - maryana maryana; Erwan Erwan (Ilmiah Institut Citra Internasional, 2020)
Spiritual care is important for patients. The only healing source for terminal patients is their spirituality. But in nursing service is still focused on the physical aspect. The purpose of this study was to explore the nurse's perception of spiritual care in the Intensive Care Unit (ICU) Hospital of Medika Stannia Sungailiat. Type of qualitative research with phenomonology approach. Informant 10 people with non purposive sampling technique. Data collection techniques, interviews and observation. 5 theme of nurse perception about spiritual care, that is understanding of nurse about spiritual care, nurse way of identifying patient's spiritual needs, spiritual care implementation, various obstacles in the implementation of spiritual care, and hope toward spiritual care. advocate in making policy in the hospital about the obligation of nurses to carry out spiritual care, counseling efforts in improving knowledge, and continuous evaluation in carrying out spiritual care in the room.